2023
DOI: 10.1007/s11764-023-01472-4
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of mental health service utilisation in people with cancer compared with people without cancer: analysis of the Australian National Study of Mental Health and Wellbeing

Huah Shin Ng,
Bogda Koczwara,
Lisa Beatty

Abstract: Purpose To compare the patterns of mental health service utilisation between people with and without cancer. Methods We performed a cross-sectional study using data of all respondents aged ≥ 25 years from the Australian National Study of Mental Health and Wellbeing 2020–2021 conducted during the COVID-19 pandemic. Comparisons were made between the two groups (cancer versus non-cancer) using logistic regression models. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Studies from Australia have shown that despite a higher prevalence of mental distress, cancer survivors underutilise mental health services. 20,32 Only one-third of cancer survivors are offered mental health support at the time of diagnosis, and many reported being unable to access or afford the psychological services they required. 20 The reasons identified for underutilisation of mental health services were low perceived need, affordability, mental health stigma and lack of care coordination.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from Australia have shown that despite a higher prevalence of mental distress, cancer survivors underutilise mental health services. 20,32 Only one-third of cancer survivors are offered mental health support at the time of diagnosis, and many reported being unable to access or afford the psychological services they required. 20 The reasons identified for underutilisation of mental health services were low perceived need, affordability, mental health stigma and lack of care coordination.…”
Section: Discussionmentioning
confidence: 99%